(untitled) (Vietnam Journal of Community Medicine, 2026)
Objectives: To determine the prevalence and some factors associated with acute-on-chronic liver failure (ACLF) in patients with acute decompensated cirrhosis at Can Tho Central General Hospital. Methods: A cross-sectional descriptive study was conducted on 130 patients with acute decompensated cirrhosis at Can Tho Central General Hospital from June 2025 to February 2026. The diagnosis of acute-on-chronic liver failure and acute decompensated cirrhosis was based on the 2023 European Association for the Study of the Liver (EASL) criteria, and ACLF grading was based on the CLIF-OF score (EASL Clinical Practice Guidelines on acute-on-chronic liver failure, 2023). Results: The proportions of patients diagnosed with acute decompensation due to ascites, gastrointestinal bleeding, hepatic encephalopathy, and infection were 66.2%, 40%, 32.3%, and 47.7%, respectively. Forty-four patients (33.8%) developed acute-on-chronic liver failure (ACLF). The incidence rates of ACLF grades 1, 2, and 3 were 20.7%, 6.15%, and 6.91%, respectively. Patients with the number of acute decompensation manifestations ≥ 2, AST levels ≥ 120 U/L, ALT levels ≥ 120 U/L, and serum sodium < 135 mmol/L had a significantly increased risk of developing ACLF (p < 0.05). Multivariate analysis showed that having ≥ 2 acute decompensation manifestations was the only independent risk factor associated with ACLF (OR = 5.95; p = 0.001). Conclusion: The number of acute decompensation manifestations is an independent risk factor for acute-on-chronic liver failure; therefore, it is necessary to promptly identify acute decompensation manifestations in cirrhotic patients.